OCCURRENCE OF THE CRAB CALAPPA LOPHOS (HERBST) IN TRAWLER LANDINGS AT SASSOON DOCKS, BOMBAY - Aravindakshan, M; Sundaram, K S (Indian Journal of Fisheries, 2011)
An instance of the crab Calappa lophos suddenly appearing in commercial quantities in the trawl catches at Sassoon dock, successively in two years, is reported.